Figurative Language as Cultural Commentary and Identity Construction: A Semiotic Analysis of Lana Del Rey's Contemporary Song Lyrics - Pratiwi, Apriana; Rosadi, Pendi (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Figurative language in contemporary popular music serves not only as aesthetic embellishment, but also as cultural commentary and a mechanism for identity formation. This study analyzes how linguistic devices operate in Lana Del Rey's songs “Summertime Sadness” and “Brooklyn Baby” to understand their role in post-recession American culture. This research employs a qualitative interpretive methodology with semiotic analysis, analyzing the official lyrics through three stages: identification, interpretation, and integration of figurative language elements. The results identify main categories of figurative language with distinct patterns: “Summertime Sadness” uses metaphors and comparisons to convey emotional intensity through light-dark contrasts, while “Brooklyn Baby” employs allusions and irony for cultural identity formation. Semiotic analysis shows that these expressions reflect post-recession America (2011–2014), functioning as cultural critique and identity negotiation. The study concludes that figurative language operates as a sophisticated meaning-making system, revealing popular music as a cultural discourse space that combines artistic expression, identity formation, and cultural critique.